Pre-Service Chemistry Teachers’ Attitude of Socio-Scientific Issues and Characters as Citizens - Anwar, Lenny; Alimin, Masnaini; Copriady, Jimmi; Rery, R.Usman; Syofni (Universitas Negeri Semarang, 2024)
This study investigates the character, and value as a citizen and attitude of socio-scientific issues (SSI) among pre-service chemistry teacher’s in Riau, Indonesia. SSI learning was conducted in the classroom and designed to cultivate characteristics and attitude of SSI. The integration of SSI with the learning process involved instruction that inquiry analyzing based on environmental issues. A total seventy-six chemistry education majors participated in the study, including eleven male and sixty-five female students. Data were collected through a structured questionnaire that measured the participants’ characteristics, civic value, and attitude of SSIs. The collected data were analyzed using SPSS 26 with, employing descriptive statistic and Mann-Whitney U analysis. The result revealed that male pre-service chemistry teacher group has a higher score in character, value as citizens, and attitude of SSI compared to their female counterparts. However, the analysis showed no statistically significant difference (p>.05) between male and female pre-service chemistry teacher in the sub-factors of character and SSI attitudes. Despite the lack of significant gender differences, the findings suggest that the integration of SSI in chemistry education can enhance moral thinking and decision-making abilities and positive attitude toward SSI. Teachers may consider both subject matter and instructional method when addressing these aspects in the classroom.